The Adventure of Tintin - Herge (Egmont Publishing Ltd, 2007)
All of Herge's original Tintin comics are now included in this hardback set. This volume includes Tintin and alph-art, which is Tintin's last adventure.
Keywords: Comics & Graphic Novels; General; Juvenile Fiction